An international study of ethics - Lane, Michael S. (International journal of value-based management, 1991)
This study presents the results of a survey of graduate students from three cultural backgrounds. English, German, and American business students responded to an eleven-item survey designed to assess one's beliefs about what is necessary to succeed in graduate business programs. The results indicate that the attributes which students believe are required to succeed differ among cultures, with the greatest differences occurring between the American and European respondents.